Investigating the use of text messages in mobile learning. (March 2013) - Geng, Gretchen
Nowadays, teaching and learning have been shifted from traditional classrooms to technology-supported learning environment. By offering a convenient, efficient and financially affordable information technology learning environment, mobile learning is a topic that is of considerable interest for education audiences owing to the pervasive nature of text messaging. This study investigated tertiary students' use of text messaging in mobile learning and related areas such as their literacy levels and years of using text messages. Given the use of such technology in classrooms today, this study is timely and makes its contribution to what is naturally scant literature in this area. Data were gathered by way of a questionnaire and text message exercises. Fifty-three students participated in this study. The results shed light on whether or not text messaging is positively or negatively related to students' self-rated reading and writing attainment. Also revealed is whether or not there are differences between students at different levels, that is, whether first-year undergraduate students use text messaging differently, and if so in what ways, than undergraduate students who are nearer the end of their studies and postgraduate students. This article offers insight into the implications of successful mobile learning upon a contemporary account of practices and how we educators might use text messaging in mobile learning.